Synthesis of One Dimensional Gold Nanostructures. (4th January 2011) - Li, Hongchen; Kan, Caixia; Yi, Zhaoguang; Ding, Xiaolong; Cao, Yanli; Zhu, Jiejun
Abstract : Gold nanostructures with shapes of rod, dumbbells, and dog bone have been fabricated by an improved seed-mediated method. It is found that the pH change (the addition of HNO3 or HCl) and the presence of Ag + ions have a great influence on the growth process and aspect ratios of these Au nanocrystals. UV-Vis-NIR absorption spectra for the Au colloidal show that the transverse plasmon absorption band locates at ~520 nm, while the longitudinal plasmon absorption band shifts in a wide spectra region of 750–1100 nm. The obtained Au nanostructures have been investigated by transmission electron microscopy, high-resolution transmission electron microscopy, and X-ray diffractometer. Based on the characterizations and FDTD simulations, most of the obtained Au nanorods are single crystals, possessing an octagonal cross-section bounded by{ 110 } and{ 100 } faces. One model for the anisotropic growth has been proposed. It is found that slow kinetics favor the formation of single-crystalline Au nanorods.